Social Media Marketing and TOE Framework Exploration in Digital Micro or Small and Medium Enterprises - Wilma Cordelia Izaak; Theodora Cicelia Khristi; Nuruni Ika Kusumawardhani (Journal of Economics, Business, and Government Challenges, 2022)
This study aims to determine the function and role of digital MSMEs stands for Micro or Small-Medium Enterprises using TOE exploration during the Covid-19 pandemic. The Covid-19 pandemic has made the majority of the economic sector, especially MSMEs, decline. The majority of MSMEs actors cannot develop and many ended up in bankruptcy. This is what makes MSMEs business actors change the function and role of digital MSMEs during the COVID-19 pandemic with a sales strategy through a digitalization scheme. The digitization scheme is by utilizing a market place (intermediary) and using social media as a marketing technique. In addition, digital MSMEs actors must be able to synergize with consumers in marketing products and services. Thus the digital MSMEs development scheme can be an alternative to save business actors in the midst of the Covid-19 pandemic. This article uses the literature study method by elaborating various literatures on the development of digital MSMEs. This article argues that the development of digital MSMEs has become an alternative to saving as well as developing the functions and roles of digital MSMEs during the COVID-19 pandemic.